2009
DOI: 10.1111/j.1524-4725.2009.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pretrichial Browlift Technique and Review of Methods and Complications

Abstract: Browlifts are an important procedure in rejuvenating the upper third of the face and improving the overall facial aesthetic appearance. The pretrichial browlift is a less invasive open technique that is safe and effective for the appropriate patient. The authors have indicated no significant interests with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…The scar can be hidden in the brow hairs if performed in appropriate patients with thick brows. Paresthesias and numbness associated with damage to the supraorbital nerve are common complications of the procedure [7]. Transient decreases in sensation are often associated with divisions of smaller branches of the nerves, which typically resolve in several months [9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The scar can be hidden in the brow hairs if performed in appropriate patients with thick brows. Paresthesias and numbness associated with damage to the supraorbital nerve are common complications of the procedure [7]. Transient decreases in sensation are often associated with divisions of smaller branches of the nerves, which typically resolve in several months [9].…”
Section: Discussionmentioning
confidence: 99%
“…Transient decreases in sensation are often associated with divisions of smaller branches of the nerves, which typically resolve in several months [9]. Damage to the supraorbital nerve and vessels can be prevented by a dissection performed superficially to the frontalis muscle [7]. Booth and colleagues reported that 74% of patients experienced numbness and that 7% of patients were dissatisfied with this complication [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations